Prova nova em fase recursal no processo penal - Lapetina, Vinícius Scatigno (2021)
This research aims to deepen the discussion on the importance of evidence in criminal proceedings. Along these lines, issues relating to the format of the criminal procedure and the moment in which evidence can be presented by the parties and appreciated by the judge will be addressed. The discussion carried out in this work will take into account not only the formal aspect of the process, governed by the rules provided for in the Code of Criminal Procedure, but will also consider the right to defense and the dignity of the human person. In this sense, I propose a reflection on the possibility of analyzing evidence presented at inappropriate moments in criminal proceedings. The conflict of constitutional principles, such as due legal process versus the right of defense, can guide deep discussions on the theme of proof in criminal proceedings. This work will not ignore this issue, especially when dealing with the appearance of evidence during the processing of appeals taken to the second and third degree courts under the jurisdiction of the Judiciary. If the appropriate time for the production and presentation of evidence in the process, according to the Code of Criminal Procedure, takes place during the investigation, destined for the lower court, after all, the judge will form his conviction by the free assessment of the evidence produced in a court case, the The appearance of evidence on appeal may seem to be a problem, and this issue deserves to be debated. If it is also true that the criminal process must approach the truth of the facts by the evidence produced, as a premise to reach a fairer trial, the emergence of new evidence in the appeal stage may put this premise in conflict with the rules in a manner provided. in the adjective criminal law, a point that will also deserve to be debated. Finally, the theme of this work reaches constitutional and infra-constitutional principiological and normative questions. At the center of the discussion is the evidence in the criminal process, its concept, its characteristics, the moment of its emergence for the process and the possibility of its appreciation by the criminal court in the appellate instances